Problematika Kurikulum Merdeka Di Kabupaten Nabire - Ismawati, Ika (Jayapangus Press, 2022)
This research trying to reveal some problems faced by teachers in the Nabire District - Central Papua. A remote area far from the city center of Indonesia. Sometimes we forget that Nabire district also need encouragement and equality. The presence of the independent curriculum seems to have shaken the teachers at Nabire because the remaining problems from the previous curriculum have not been resolved and are now given a new burden with the new curriculum too. The data for this paper comes from the opinions of teachers in Nabire district who really understand the conditions at Nabire. This research reviews the concept of learning in the independent curriculum and also the complementation of the independent curriculum in Central Papua. This research was conducted using observation, interviews and document study method. Data was obtained through informants selected using purposive sampling. All data was then analyzed descriptively qualitatively using Rodan and Nurkse’s Bersa Nudge Theory. The results of the analysis show that the independent curriculum is very good curriculum and is able to provide optimal development for students. However, the independent curriculum is still far from ready to be implemented in Nabire district, which is still underdeveloped. Underdeveloped means the number of teacher is unequal, there is a lack of infrastructure and there are still many students who are isolated and trapped by extreme geographical conditions. In fact, there are still students who are hampered by long distances to school. Therefore, the implementation of the independent curriculum can be implemented well for students and teachers will not face difficulties in implementing the independent curriculum.